Sintesis dan Karakterisasi Dolomit Nanopartikel Tinggi CaO-MgO Sebagai Bahan Baku Penyerap Logam Berat - Muhaiyat Syah (Jurnal Serambi Engineering, 2022)
The use of dolomite mineral rock as an adsorbent to absorb heavy metal waste is of particular concern to be handled properly so that there is no danger and damage to the environment. This research will handle the removal of heavy metals, especially iron (Fe) with a batch process. The use of dolomite mineral rock as an adsorbent is expected to be able to absorb heavy metals well after synthesizing the adsorbent into nanoparticle size. The aim of this research is to find out the characteristics of the dolomite adsorbent which will be used as the raw material for the absorption of Fe metal ions. The synthesis of dolomite nanoparticles was carried out using the co-precipitation method, then a physical activation process was carried out at a temperature of 9000C to obtain a nanoparticle-sized dolomite adsorbent and then the characteristics of dolomite nanoparticles were determined using SEM-EDX, XRD and FTIR. The results of SEM-EDX characterization gave an even distribution of particles and fine pores with the highest chemical content of MgO and CaO of 22.74 and 19.33%, respectively. The XRD characterization of the highest diffraction peak at an angle of (2θ) 37.30o with an intensity of 1444 contained MgO compounds and an average crystal diameter of 40,726 nm. The FTIR characterization of the wave number 771.53 cm-1 indicated that the CaC functional group had broad intensity, while the wave number 877.62 cm-1 contained a sharp intensity Mg-C functional group.